Reorganization of sensory networks after subcortical vestibular infarcts: A longitudinal symptom‐related voxel‐based morphometry study. (8th February 2022) - Conrad, Julian; Habs, Maximilian; Ruehl, Ria Maxine; Boegle, Rainer; Ertl, Matthias; Kirsch, Valerie; Eren, Ozan Emre; Becker‐Bense, Sandra; Stephan, Thomas; Wollenweber, Frank Arne; Duering, Marco; Dieterich, Marianne; et al.
Abstract: Background and purpose: We aimed to delineate common principles of reorganization after infarcts of the subcortical vestibular circuitry related to the clinical symptomatology. Our hypothesis was that the recovery of specific symptoms is associated with changes in distinct regions within the core vestibular, somatosensory, and visual cortical and subcortical networks. Methods: We used voxel‐ and surface‐based morphometry to investigate structural reorganization of subcortical and cortical brain areas in 42 patients with a unilateral, subcortical infarct with vestibular and ocular motor deficits in the acute phase. The patients received structural neuroimaging and clinical monitoring twice (acute phase and after 6 months) to detect within‐subject changes over time. Results: In patients with vestibular signs such as tilts of the subjective visual vertical (SVV) and ocular torsion in the acute phase, significant volumetric increases in the superficial white matter around the parieto‐opercular (retro‐)insular vestibular cortex (PIVC) were found at follow‐up. In patients with SVV tilts, spontaneous nystagmus, and rotatory vertigo in the acute phase, gray matter volume decreases were located in the cerebellum and the visual cortex bilaterally at follow‐up. Patients with saccade pathology demonstrated volumetric decreases in cerebellar, thalamic, and cortical centers for ocular motor control. Conclusions: The findings support the role of the PIVC as the key hub for vestibular processing and reorganization. The volumetric decreases represent the reciprocal interaction of the vestibular, visual, and ocular motor systems during self‐location and egomotion detection. A modulation in vestibular and ocular motor as well as visual networks was induced independently of the vestibular lesion site. Abstract : Using longitudinal voxel‐ and surface‐based morphometry, this study demonstrates structural reorganization after ischemic infarcts with vestibular and ocular motor symptoms. The findings highlight the role of the subcortical white matter around the parieto‐opercular (retro‐)insular vestibular cortex as a core region for structural reorganization of cortical vestibular processing.